Electrolyte Materials

By using sulfide solid electrolytes and fluoride polymers in electrolyte materials, the particle size and content are optimized, and the problem of insufficient conductivity of existing electrolyte materials is solved, achieving higher ionic conductivity and better battery performance.

JP7655290B2Active Publication Date: 2025-04-02TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022141501
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-06
Publication Date
2025-04-02
Estimated Expiration
2042-09-06

AI Technical Summary

Technical Problem

There is still room for improvement in the existing electrolyte materials to improve polymer conductivity, especially when using sulfide solid electrolytes, particle size and content need to be optimized to improve ionic conductivity.

Method used

The sulfide solid electrolyte and fluoride polymer are used as the electrolyte materials. The average particle size of the sulfide solid electrolyte is controlled below 0.2 microns, with a content between 20% and 90%, and the fluoride polymer is used as the binding agent.

Benefits of technology

It significantly improves the ionic conductivity of the electrolyte material, is suitable for separation membranes and electrode materials of solid-state batteries, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655290000002
    Figure 0007655290000002
  • Figure 0007655290000003
    Figure 0007655290000003
  • Figure 0007655290000001
    Figure 0007655290000001
Patent Text Reader

Abstract

To provide an electrolyte material having high ionic conductivity.SOLUTION: In an electrolyte material containing a sulfide solid electrolyte and a polymer, the average particle size of the sulfide solid electrolyte is less than 0.2 μm, the content of the sulfide solid electrolyte in the electrolyte material is 20 mass% or more and less than 90 mass%, the polymer includes a dispersion medium and binder particles, and the binder particle group includes a fluorine-containing polymer material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to electrolyte materials. [Background technology]

[0002] Patent Document 1 (JP Patent Publication No. 2019-503050) discloses an electrolyte material including ion-conductive ceramic particles dispersed in a matrix of an ion-conductive solid polymer, an electrolyte salt, and a chemical additive. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2019-503050 Summary of the Invention [Problem to be solved by the invention]

[0004] The electrolyte material described in Patent Document 1 contains an ionically conductive solid polymer and ionically conductive ceramic particles, which makes it possible to improve the conductivity of a polymer material that has low conductivity. However, there is room for improvement in the conductivity.

[0005] It is therefore an object of the present disclosure to provide an electrolyte material having high ionic conductivity. [Means for solving the problem]

[0006] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.

[0007] [1] An electrolyte material comprising a sulfide solid electrolyte and a polymer, The sulfide solid electrolyte has an average particle size of less than 0.2 μm; The content of the sulfide solid electrolyte in the electrolyte material is 20% by volume or more and less than 90% by volume, The polymer includes a dispersion medium and a binder particle group, The binder particle group includes a fluorine-containing polymer material.

[0008] Generally, polymers have low ionic conductivity, so adding a solid electrolyte improves the ionic conductivity. Among solid electrolytes, it is considered preferable to use a sulfide solid electrolyte having high ionic conductivity. In addition, from the viewpoint of reactivity with the sulfide solid electrolyte, a fluorine-containing polymer material is suitable as the binder particle group in the polymer.

[0009] On the other hand, the ionic conductivity may decrease depending on the size and content of the sulfide solid electrolyte. Therefore, it is considered necessary to set the size and content of the sulfide solid electrolyte within a predetermined range.

[0010] [2] The sulfide solid electrolyte is represented by the following formula (1): vLiI-wLiBr-(100-vw)(Li 2 SP 2 S 5 ) (1) having a composition represented by In the above formula (1), v represents the mole fraction percentage of the component derived from LiI and satisfies the relationship of 10≦v≦20; w represents the mole fraction percentage of the component derived from LiBr and satisfies the relationship of 0≦w≦15; (100-vw) is Li 2 SP 2 S 5 The electrolyte material according to [1], wherein the percentage of the molar fraction of the component derived from

[0011] [3] The dispersion medium contains butyl acetate, The electrolyte material according to [1] or [2], wherein the binder particles include polyvinylidene fluoride.

[0012] [4] An electrolyte material comprising a sulfide solid electrolyte and a polymer, The sulfide solid electrolyte has an average particle size of 0.1 μm or less, The content of the sulfide solid electrolyte in the electrolyte material is 30% by volume or more and 80% by volume or less, The sulfide solid electrolyte has the following formula (1): vLiI-wLiBr-(100-vw)(Li 2 SP 2 S 5 ) (1) having a composition represented by In the above formula (1), v represents the mole fraction percentage of the component derived from LiI and satisfies the relationship of 10≦v≦20; w represents the mole fraction percentage of the component derived from LiBr and satisfies the relationship of 0≦w≦15; (100-vw) is Li 2 SP 2 S 5 indicates the mole fraction percentage of the component derived from The dispersion medium comprises butyl acetate, The binder particles include polyvinylidene fluoride. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic diagram showing the electrolyte material of the present embodiment. [Diagram 2] FIG. 2 is a conceptual diagram showing the all-solid-state battery in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure.

[0015] <Electrolyte materials> The electrolyte material of the present embodiment may be used, for example, to form a separator of an all-solid-state battery. However, the electrolyte material of the present embodiment may be applied to any application. The electrolyte material of the present embodiment may be used, for example, to form an electrode of an all-solid-state battery.

[0016] 1 is a schematic diagram showing an electrolyte material of the present embodiment. The electrolyte material 5 includes a sulfide solid electrolyte 1 and a polymer 2. In the electrolyte material 5, the sulfide solid electrolyte 1 may be dispersed inside the polymer 2. Hereinafter, the solid electrolyte may be abbreviated as "SE" and the sulfide solid electrolyte may be abbreviated as "sulfide SE".

[0017] (Sulfide solid electrolyte) The sulfide SE has high ionic conductivity. The sulfide SE can form an ionic conduction path in the electrolyte material. The sulfide SE includes sulfur (S). The sulfide SE may further include, for example, lithium (Li) or phosphorus (P). The sulfide SE may further include, for example, oxygen (O), silicon (Si), or the like. The sulfide SE may further include, for example, a halogen, such as iodine (I) or bromine (Br).

[0018] The sulfide SE may be, for example, in a glass state. The sulfide SE may form, for example, a glass ceramic (also called "crystallized glass").

[0019] The sulfide SE can be synthesized by a mechanochemical method. For example, raw materials may be mixed by a planetary ball mill, an ultrasonic dispersing device, or the like. In the mechanochemical method, mechanical energy is applied to the mixture, so that the composition of the mixture becomes uniform and the mixture can become in a glassy state. Furthermore, glass ceramics can be formed by subjecting the mixture in the glassy state to an appropriate heat treatment.

[0020] The composition of the sulfide SE is expressed by the mole fraction of the raw materials. The raw materials are lithium phosphorus sulfide (e.g., Li 2 SP 2 S5 etc.) and lithium halides (e.g., lithium iodide (LiI), lithium bromide (LiBr), etc.).

[0021] The composition of the sulfide SE may be represented, for example, by the following formula (1). vLiI-wLiBr-(100-vw)(Li 2 SP 2 S 5 ) (1) In the above formula (1), "v" indicates the molar fraction (mol%) of the component derived from LiI. "v" may satisfy the relationship of, for example, "10≦v≦20". For example, when "v=10", it indicates that the molar fraction of LiI is 10 mol% with respect to the entire raw material.

[0022] "w" indicates the molar fraction of the component derived from LiBr. "w" may satisfy the relationship of "0≦w≦15", for example. For example, when "w=10", the molar fraction of LiBr is 10 mol% with respect to the entire raw material.

[0023] "(100-vw)" is Li 2 SP 2 S 5 For example, in the case of "v=w=10", the mole fraction of Li is 2 SP 2 S 5 This indicates that the mole fraction is 80 mol%.

[0024] The sulfide SE is, for example, 10LiI-10LiBr-80 (Li 2 SP 2 S 5 ), 15LiI-5LiBr-80(Li 2 SP 2 S 5 ), 10LiI-15LiBr-75(Li 2 SP 2 S 5 ), 15LiI-10LiBr-75(Li 2 SP 2 S 5), 20LiI-5LiBr-75(Li 2 SP 2 S 5 ) etc.

[0025] Li 2 SP 2 S 5 Lithium sulfide (Li 2 S) and diphosphorus pentasulfide (P 2 S 5 Lithium phosphorus sulfide can be produced by mechanochemical reaction with Li 3 P.S. 4 , Li 4 P 2 S 6 , Li 7 P 3 S 11 The composition may be the same as above.

[0026] The composition of lithium phosphorus sulfide may also be expressed in terms of the mole fraction of the raw materials. 2 S and P 2 S 5 The mixture ratio is arbitrary. For example, "0.75Li 2 S-0.25P 2 S 5 " In the case of Li 2 The mole fraction of the component derived from S is 0.75 with respect to the entire raw material of lithium phosphorus sulfide, and P 2 S 5 The mole fraction of the component derived from the lithium phosphorus sulfide raw material is 0.25. Note that the mole fraction of the lithium phosphorus sulfide raw material (Li 2 S and P 2 S 5 The sum of (and ) is defined as 1.00.

[0027] The composition of the lithium phosphorus sulfide may be represented, for example, by the following formula (2). uLi 2 S-(1-u)P 2 S 5 (2) In the above formula, "u" is Li 2The mole fraction of the component derived from S. "(1-u)" is the mole fraction of P 2 S 5 "u" may satisfy the relationship of, for example, "0.5≦u≦0.9".

[0028] Lithium phosphorus sulfide, for example, 0.5Li 2 S-0.5P 2 S 5 ,0.6Li 2 S-0.4P 2 S 5 , 0.7Li 2 S-0.3P 2 S 5 , 0.75Li 2 S-0.25P 2 S 5 , 0.8Li 2 S-0.2P 2 S 5 , 0.9Li 2 S-0.1P 2 S 5 etc.

[0029] The average particle size (D50) of the sulfide SE is less than 0.2 μm. When the D50 of the sulfide SE is less than 0.2 μm, the sulfide SE is easily dispersed inside the polymer. The D50 of the sulfide SE is preferably 0.1 μm or less. The lower limit of the D50 of the sulfide SE is not particularly limited, but may be, for example, 0.01 μm or more from the viewpoint of production. Here, D50 indicates the particle size at which the cumulative frequency from the small particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method.

[0030] The content of sulfide SE in the electrolyte material is 20% by volume or more and less than 90% by volume. If the content of sulfide SE in the electrolyte material is less than 20% by volume, it is difficult to form an ion conduction path in the electrolyte material, so that the ion conductivity may decrease. If the content of sulfide SE in the electrolyte material is 90% by volume or more, the content of sulfide SE is too high and the electrolyte material may not be formed. The content of sulfide SE in the electrolyte material is preferably 30% by volume or more and 80% by volume or less.

[0031] (polymer) The polymer includes a dispersion medium and a binder particle group. The polymer may be substantially composed of a dispersion medium and a binder particle group. The polymer may be composed of, for example, 15% by mass or less of the binder particle group and the remainder being a dispersion medium. By having the mass fraction of the binder particle group be 15% by mass or less, appropriate fluidity and dispersion stability are expected. The polymer may be composed of, for example, 1% by mass to 15% by mass of the binder particle group and the remainder being a dispersion medium.

[0032] The dispersion medium is a liquid. The dispersion medium may contain any component. The dispersion medium may contain, for example, a carboxylate ester. The dispersion medium may contain, for example, ethyl acetate, butyl acetate, butyl butyrate, pentyl butyrate, butyl pentanoate, pentyl pentanoate, butyl hexanoate, pentyl hexanoate, etc. It is preferable that the dispersion medium contains butyl butyrate. The dispersion medium may be substantially composed of butyl butyrate. Butyl butyrate tends to have low reactivity with sulfide SE.

[0033] The binder particles are a dispersoid. The binder particles are dispersed in a dispersion medium. The binder particles can bond objects together.

[0034] In the binder particle group, each of the particles contains a fluorine-containing polymer material. That is, the binder particle group contains a fluorine-containing polymer material. Each of the particles may be substantially made of a fluorine-containing polymer material. That is, the binder particle group may be substantially made of a fluorine-containing polymer material.

[0035] The fluorine-containing polymer material may contain, for example, a structural unit derived from vinylidene fluoride (VdF). In this embodiment, the term "structural unit" refers to an atomic group that constitutes a part of the basic structure of a polymer chain. The smallest structural unit that constitutes a regular molecular chain by its repetition is also particularly referred to as a "structural repeat unit."

[0036] The fluorine-containing polymer material may be, for example, a homopolymer. That is, the fluorine-containing polymer material may be, for example, polyvinylidene fluoride (PVdF). PVdF is substantially composed of constituent repeating units derived from VdF.

[0037] The fluorine-containing polymer material may be, for example, a copolymer. That is, the fluorine-containing polymer material may contain a structural unit other than the structural unit derived from VdF. The fluorine-containing polymer material may contain, for example, a structural unit derived from tetrafluoroethylene (TFE) or a structural unit derived from hexafluoropropene (HFP). The copolymer may be, for example, a random copolymer, an alternating copolymer, a block copolymer, or a graft copolymer.

[0038] The molecular weight of the fluorine-containing polymer material can be measured, for example, by gel permeation chromatography (GPC). The polymer material may have a weight average molecular weight (standard polystyrene equivalent) of, for example, 100,000 to 2,000,000.

[0039] <All-solid-state battery> 2 is a conceptual diagram showing an all-solid-state battery in this embodiment. The all-solid-state battery 100 may include, for example, an exterior body (not shown). The exterior body may be, for example, a pouch made of a metal foil laminate film. The exterior body may house a power generating element 50. The power generating element 50 includes a positive electrode 10, a separator layer 30, and a negative electrode 20. That is, the all-solid-state battery 100 includes a positive electrode 10, a separator layer 30, and a negative electrode 20.

[0040] <Separator layer> The separator layer 30 is interposed between the positive electrode 10 and the negative electrode 20. The separator layer 30 separates the positive electrode 10 from the negative electrode 20. The separator layer 30 blocks the movement of electrons between the positive electrode 10 and the negative electrode 20. The separator layer 30 may have any thickness. The separator layer 30 may have a thickness of, for example, 1 to 100 μm. The separator layer 30 includes an electrolyte material. Details of the electrolyte material are as described above.

[0041] 《Positive electrode》 The positive electrode 10 may include a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector may include, for example, an aluminum (Al) foil. The positive electrode current collector may have a thickness of, for example, 5 to 50 μm.

[0042] The positive electrode active material layer may have a thickness of, for example, 10 to 200 μm. The positive electrode active material layer is in close contact with the separator layer 30. The positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer may further contain a sulfide SE, a conductive material, a binder, and the like.

[0043] The positive electrode active material may be, for example, in a particulate form. The positive electrode active material may have, for example, a D50 of 1 to 30 μm. The positive electrode active material may be, for example, LiCoO 2 , LiNiO 2 , LiMnO 2 , Li(NiCoMn)O 2 , and Li(NiCoAl)O 2 For example, "Li(NiCoMn)O 2 "(NiCoMn)" in "(NiCoMn)" indicates that the sum of the composition ratios in the parentheses is 1. The amount of each component is arbitrary as long as the sum is 1. The positive electrode active material may be subjected to a surface treatment. A buffer layer may be formed on the surface of the positive electrode active material by the surface treatment. The buffer layer may be, for example, lithium niobate (LiNbO 3 The buffer layer is expected to reduce the battery resistance.

[0044] The details of the sulfide SE are as described above. The blending amount of the sulfide SE may be, for example, 1 to 100 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0045] The conductive material may contain, for example, vapor-grown carbon fiber (VGCF) or the like. The binder may contain, for example, PVdF or the like. The blending amounts of the conductive material and the binder particle group may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0046] The negative electrode 20 may include a negative electrode current collector and a negative electrode active material layer. The negative electrode current collector may include, for example, a copper (Cu) foil, a nickel (Ni) foil, or the like. The negative electrode current collector may have a thickness of, for example, 5 to 50 μm.

[0047] The negative electrode active material layer may have a thickness of, for example, 10 to 200 μm. The negative electrode active material layer is in close contact with the separator layer 30. The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer may further contain a sulfide SE, a conductive material, a binder, and the like.

[0048] The negative electrode active material may be, for example, particulate. The negative electrode active material may have a D50 of, for example, 1 to 30 μm. The negative electrode active material may contain at least one selected from the group consisting of graphite, Si, silicon oxide [SiO x (0 < x < 2)], and lithium titanate.

[0049] The details of the sulfide SE are as described above. The blending amount of the sulfide SE may be, for example, 1 to 100 parts by mass with respect to 100 parts by mass of the negative electrode active material.

[0050] The conductive material may contain, for example, VGCF or the like. The binder particle group may contain, for example, PVdF or the like. The blending amounts of the conductive material and the binder particle group may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the negative electrode active material.

Examples

[0051] The present embodiment will be described below using examples, but the present embodiment is not limited to these.

[0052] No.1-1~1-5 (Separator) Sulfide SE: 15LiI-10LiBr-75(Li 2 SP 2 S 5 ) (glass ceramic type, D50 = 0.1 μm), butyl acetate as a dispersion medium, and PVdF powder as a binder particle group were prepared. 2 SP 2 S 5 ) is more specifically "0.75Li 2 S-0.25P 2 S 5 " It was.

[0053] A polypropylene (PP) container was prepared. A dispersion medium and binder particles were placed in the PP container so that the concentration of the binder particles was 5% by mass. A stirrer (PC-420D, manufactured by Corning Incorporated) was placed in the PP container, and the mixture was stirred for 12 hours. As a result, a polymer was obtained.

[0054] The polymer, sulfide SE, and dispersion medium were placed in a PP container so that the sulfide SE content was the value shown in Table 1. The above materials were stirred for 30 seconds using an ultrasonic dispersion device (UH-50, manufactured by SMT Corporation). After stirring, the PP container was placed in a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.) and shaken for 3 minutes. This resulted in the production of an electrolyte material.

[0055] A temporary support (Al foil) was prepared. The electrolyte material was applied to the surface of the temporary support using a doctor blade applicator. The electrolyte material was dried for 3 hours on a hot plate. The hot plate was set to a temperature of 130°C. As a result, a separator layer was formed on the surface of the temporary support.

[0056] (Test battery) Positive and negative electrodes were prepared. The separator, positive and negative electrodes were punched into disk shapes. The separator had a diameter of 16 mm, and the positive and negative electrodes had diameters of 19 mm. 2032k type positive and negative electrode cans were prepared. The negative electrode, separator, positive electrode, SUS spacer and SUS washer were stacked in this order between the negative and positive electrode cans from the negative can to the positive can. After placement, they were pressed for 3 seconds with a coin press machine to produce coin batteries, which were test batteries No. 1-1 to 1-5.

[0057] No.2-1~2-5 Coin batteries, which were test batteries, were produced in the same manner as Nos. 1-1 to 1-5, except that the D50 of the sulfide SE was set to 0.5 μm.

[0058] No.3-1~3-5 Coin batteries, which were test batteries, were produced in the same manner as Nos. 1-1 to 1-5, except that the D50 of the sulfide SE was set to 1.0 μm.

[0059] No.4-1~4-5 Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was prepared. The above-mentioned polymer and LiTFSI were placed in a PP container so that the concentration of LiTFSI was 0.3 mass%. The above material was stirred for 30 seconds by the ultrasonic dispersion device. Thus, an electrolyte material was obtained.

[0060] A temporary support (Al foil) was prepared. An electrolyte material was applied to the surface of the temporary support using a doctor blade applicator and dried at room temperature for 12 hours. The electrolyte material was then dried on a hot plate for 3 hours. The hot plate was set at a temperature of 130°C. As a result, a separator layer was formed on the surface of the temporary support. Then, coin batteries, which were test batteries, were fabricated in the same manner as Nos. 1-1 to 1-5.

[0061] <Evaluation> (Ionic Conductivity) Each coin battery was left in a thermostatic chamber set at 25°C for 3 hours. Then, AC impedance measurement was performed using an electrochemical measuring device (VMP3, manufactured by Biologic Co., Ltd.). The amplitude was 10 mV. The frequency range was 0.1 to 1.0 MHz. This resulted in a Cole-Cole plot. An arc was fitted to the Cole-Cole plot. The distance between the two intersections of the fitted arc and the real axis was determined. This distance was considered to be the "interface resistance." The reciprocal of the interface resistance was considered to be the ionic conductivity. The ionic conductivity of the coin battery No. 1-1 was taken as the standard (100), and the ionic conductivities of No. 2-1, 3-1, and 4-1 were relativized and evaluated. Similarly, the ionic conductivity of the coin battery No. 1-2 was set as the reference (100) to evaluate the ionic conductivity of the coin battery No. 2-2, 3-2, and 4-2, the ionic conductivity of the coin battery No. 1-3 was set as the reference (100) to evaluate the ionic conductivity of the coin battery No. 2-3, 3-3, and 4-3, and the ionic conductivity of the coin battery No. 1-4 was set as the reference (100) to evaluate the ionic conductivity of the coin battery No. 2-4, 3-4, and 4-4. The results are shown in Table 1. In addition, in each of the coin batteries No. 1-5, No. 2-3 to 2-5, No. 3-5, and No. 4-5, the interface resistance was too large and exceeded the upper limit of measurement, so that the ionic conductivity could not be calculated.

[0062] [Table 1]

[0063] In No. 1-1 to 1-4, the ionic conductivity was high. In No. 4-4, when the amount of sulfide SE was greater than a certain amount, it became difficult to form a contact point between the sulfide SE and the active material, and as a result, the ionic conductivity decreased significantly, which is thought to be why the ionic conductivity appears to be higher.

[0064] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]

[0065] 1 sulfide solid electrolyte, 2 polymer, 5 electrolyte material, 10 positive electrode, 20 negative electrode, 30 separator layer, 50 power generating element, 100 all-solid-state battery.

Claims

[Claim 1] An electrolyte material comprising a sulfide solid electrolyte and a polymer, The sulfide solid electrolyte has an average particle size of 0.1 μm or less, The content of the sulfide solid electrolyte in the electrolyte material is 30% by volume or more and 80% by volume or less, The sulfide solid electrolyte has the following formula (1): vLiI-wLiB2-(100-v-w)Li 2 S-P 2 S 5 ) (1) having a composition represented by In the above formula (1), v represents the molar fraction percentage of the component derived from LiI, and satisfies the relationship of 10≦v≦20; w represents the molar fraction percentage of the component derived from LiBr, and satisfies the relationship of 0≦w≦15; (100-vw) is Li 2 S-P 2 S 5 indicates the mole fraction percentage of the component derived from The polymer includes a dispersion medium and a binder particle group, The dispersion medium comprises butyl acetate, The binder particles include polyvinylidene fluoride.

Citation Information

Patent Citations

  • Ceramic-polymer composite electrolytes for lithium polymer batteries.

    JP2019503050A

  • Separator for all-solid battery, manufacturing method thereof, and all-solid battery

    JP2020102310A

  • All-solid battery

    JP2021132005A

  • Binder composition, production method of binder composition and production method of solid state battery

    JP2021195374A

  • Inorganic solid electrolyte-containing composition, sheet for solid-state secondary batteries, solid-state secondary battery, and methods for producing solid-state secondary battery and sheet for solid-state secondary batteries

    WO2021039950A1